Culturally responsive ICT integration into teaching and learning [PowerPoint] - Ferdinand, Debra (My University, 2014)
This presentation notes the limited local digitized curriculum content in the Caribbean as opposed to the proliferation and easy access of US digital educational resources. It also notes that appropriate adaptation is constrained by time, know how, and resources, and that cross-cultural factors are overlooked. It therefore identifies the need to examine cross-cultural factors for making information and communication technology (ICT) integration more culturally responsive. The study sought to identify: 1) the cross-cultural factors that may impact on teaching and learning for Caribbean students; 2) how such cross-cultural factors could be used to enhance the cultural responsiveness of ICT integration into teaching and learning; and 3) the benefits of enhancing the cultural responsiveness of ICT integration into teaching and learning
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Information and communication technology; Technology integration; Cross-cultural factors; Caribbean